Problem-based Learning and Thinking Style Impact on Information Literacy Skill Improvement among Islamic Education Department Students - Gani, A; Zulaikhah, Siti; Irsyady, Kamran Asat; Siregar, Ferry Muhammadsyah (Library philosophy and practice, 2021)
The information literacy skill in Islamic Education is very important for students to achieve learning goals. Therefore, this research aims to analyze the impact of the problem-based learning model's implementation and thinking styles on information literacy skill improvement among Islamic Education Department students. This is a quasi research with data collected through test instruments as well as questionnaires, and then analyzed descriptively and inferentially. Furthermore, the data processing results of information literacy skills and thinking styles were based on the SPSS v.25 programs using two-way analysis of variance with different cells. Based on the analysis of the differences in two ways, the following were obtained (1) p-value = 0.0000 <a = 0.05, therefore H0A was rejected, hence there is an influence of the learning model on information literacy skills, (2) p-value = 0.0000 < a = 0.05, therefore H0B was rejected, and it is found that there is an influence of thinking style on information literacy skills, (3) there is no relationship between learning models and thinking styles on information literacy skills.